Hydrogel-based flexible materials for diabetes diagnosis, treatment, and management - Jiang Song (Nature Portfolio, 2021)
Abstract Diabetes is a chronic metabolic disease characterized by high glucose concentration in blood. Conventional management of diabetes requires skin pricking and subcutaneous injection, causing physical pain and physiological issues to diabetic individuals. Hydrogels possess unique advantages such as lightweight, stretchability, biocompatibility, and biodegradability, offering the opportunities to be integrated as flexible devices for diabetes management. This review highlights the development of hydrogels as flexible materials for diabetes applications in glucose monitoring, insulin delivery, wound care, and cell transplantation in recent years. Challenges and prospects in the development of hydrogel-based flexible devices for personalized management of diabetes are discussed as well.